Immediate Interventional Management of Aortocoronary Dissection During PCI: A Case Report - Nikolay Kalvachev; Veselin Valkov; Nikolay Dragnev (Cardiovascular Innovations and Applications)
Aortocoronary dissection is a rare and potentially fatal complication of percutaneous coronary intervention. It is more common when performing interventions of the right coronary artery or during revascularization of chronic total occlusions. Here, we aimed to provide more data regarding a less common form of this complication. We present the case of an 81-year old woman admitted with an acute infero-lateral myocardial infarction, who was indicated for emergency primary coronary intervention. After revascularization of the left circumflex artery, the left main coronary artery exhibited retrograde dissection into the ascending aorta. This complication was managed with immediate placement of another coronary stent at the left main coronary artery. Further propagation of the dissection was prevented. The patient was discharged in good health with antiagregant and rhythm control therapy for new onset atrial fibrillation. Although retrograde dissection of the left main coronary artery is a very rare complication, it can be successfully managed interventionally.